Kobiety, matki i dzieci specjalnej troski – problemy pedagogiczne i penitencjarne - Raś, Danuta (Chowanna, 2019)
This article concerns the analyses and research on women and men coming from penitentiary correction centres and the youth from families at risk of delinquency. The research problem concentrates on the analysis of criminals who are parents and situations of children in historical and contemporary context as well as on specific difficulties in the functioning of special-needs children in social life in terms of special education. This article can inspire a new approach to dealing with criminals, enhancing their role as parents, which constitutes an important factor in the process of corrective actions.